2005
DOI: 10.1007/s10886-005-1349-6
|View full text |Cite
|
Sign up to set email alerts
|

6-Alkylsalicylic Acids and 6-Alkylresorcylic Acids from Ants in the Genus Crematogaster from Brunei

Abstract: The defensive chemistry of two species of ants from Brunei in the genus Crematogaster (Physocrema group) has been investigated. Ants in this group release a white secretion from hypertrophied metapleural glands on their thorax when they are disturbed. Previously, one species in this group has been shown to produce alkylphenols and alkylresorcinols. In the present investigation, similar compounds along with salicylic acids and resorcylic acids that are anacardic acid and olivetolic acid homologs, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Instead, their MGs are highly developed; in fact, C. inflata has the largest known MGs (measured by secretory cell counts, Billen et al 2011). Metapleural gland chemistry has been reported for C. difformis in two reports, one using samples collected from Malaysia (Attygalle et al 1989) and the other from Brunei (Jones et al 2005). The MG chemistry of each is so unique (combinations of 6-alkylsalicylic and 6-alkylresorcylic acids, 5-alkylresorcinols and 3-alkylphenols; see Table 1, Fig.…”
Section: Crematogastermentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, their MGs are highly developed; in fact, C. inflata has the largest known MGs (measured by secretory cell counts, Billen et al 2011). Metapleural gland chemistry has been reported for C. difformis in two reports, one using samples collected from Malaysia (Attygalle et al 1989) and the other from Brunei (Jones et al 2005). The MG chemistry of each is so unique (combinations of 6-alkylsalicylic and 6-alkylresorcylic acids, 5-alkylresorcinols and 3-alkylphenols; see Table 1, Fig.…”
Section: Crematogastermentioning
confidence: 99%
“…The MG chemistry of each is so unique (combinations of 6-alkylsalicylic and 6-alkylresorcylic acids, 5-alkylresorcinols and 3-alkylphenols; see Table 1, Fig. 3) that Jones et al (2005) suggested that they are likely different species. Comparison with a third species, C. inflata (Jones et al 2005), shows a third blend of components (Table 1, Fig.…”
Section: Crematogastermentioning
confidence: 99%
See 1 more Smart Citation
“…4 Proposed biogenetic pathway for cannabinoids with C 3 side-chain of phloroglucinol glucoside in cannabis (Hammond and Mahlberg 1994) suggests a regulatory role for olivetolic acid in the biosynthesis of cannabinoids (Fig. 3), although, the presence of olivetolic acid and olivetol in ants from genus Crematogaster has been reported (Jones et al 2005); both olivetolic acid and olivetol are classified as resorcinolic lipids (alkylresorcinol, resorcinolic acid); these last ones have been detected in several plants and microorganisms (Roos et al 2003;Jin and Zjawiony 2006). Kozubek and Tyman (1999) suggested that alkylresorcinols, such as olivetol, are formed from biosynthesized alkylresorcinolic acids by enzymatic decarboxylation or via modified fatty acid-synthesizing enzymes, where the alkylresorcinolic acid carboxylic group would be expected to be also attached either to ACP (acyl carrier protein) or to CoA.…”
Section: Cannabinoid Biosynthesismentioning
confidence: 99%
“…Abbreviations: c, canaliculi; cc, collecting chamber; cut, cuticle; ep, single squamous epithelium; p, sieve plates; r, reservoir; sc, secretory cells. Modified from Vieira et al (2010). 1898; Donisthorpe, 1941;Hosoishi & Ogata, 2008), with a secretion consisting of a mixture of phenolic compounds that are harmful to predators (Attygale et al, 1989;Jones et al, 2005). Finally, Maschwitz et al (1970) and Maschwitz (1974) reported antibiotic properties of secretion produced by the metapleural gland of ants.…”
Section: Introductionmentioning
confidence: 99%